A Study of the Effect of Leadership Style towards Organizational Culture on Job Satisfaction and Employee Performance in Bangkok - Kongkaew, Wo Wilaiporn; Nuangjamnong, Chompu (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2023)
This study endeavors to explore the intricate interplay among leadership style, organizational culture, job satisfaction, and employee performance within the organizational landscape of Bangkok, Thailand. Employing a single linear regression (SLR) methodology and a blend of primary and secondary data collection techniques, the research delves into the factors influencing leadership style in the unique context of Bangkok. The investigation adopts an archival study approach, involving 395 respondents with a minimum of six months of work experience in diverse companies or organizations. To enrich the study, five theoretical frameworks from prior research are integrated to formulate a new conceptual framework. The findings underscore significant correlations between the variables under examination, revealing that leadership style significantly influences organizational culture, job satisfaction, and employee performance. Furthermore, the study unveils the pivotal role of organizational culture in shaping both employee performance and job satisfaction. While offering valuable insights, this research is not without limitations. It focuses exclusively on the impact of leadership style on organizational culture, job satisfaction, and employee performance in Bangkok, potentially constrained by time and budgetary restrictions. The study’s scope is confined to the city of Bangkok, with data derived from a sample of 395 respondents, potentially limiting its generalizability to the entire Thai population or applicability to different countries and time frames. Nevertheless, this research contributes a comprehensive and innovative framework for comprehending the dynamics of leadership style, organizational culture, job satisfaction, and employee performance within the specific organizational context in Bangkok.